Pengaruh Aktivitas Profitabilitas dan Ukuran Perusahaan Terhadap Financial Distress. - Feisol Maulana; Satria Yudhia Wijaya; Sumilir Sumilir (Jurnal Syntax Transformation, 2021)
This study aims to analyze the effect of activity, profitability and firm size on Financial Distress. This study uses data from the company property sector, real estate and building construction are listed in the Indonesia Stock Exchange (BEI) 2017-2019, with a total sample of 60 companies. Sampling in this study using a purposive sampling method. This research uses quantitative methods with hypothesis testing using multiple linear regression methods using SPSS 25 application. The result of this research is that activity and company size variables have no influence on Financial Distress, but Profitability variable has an influence on Financial Distress.